2014
DOI: 10.1007/s00431-014-2263-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition of RSV infection-related respiratory morbidity in preterm infants

Abstract: Our results suggest that prematurely born infants may have a genetic predisposition to RSV LRTIs and subsequent respiratory morbidity which is independent of premorbid lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Previous genetic studies have demonstrated a significant association between the inherited polymorphisms in several immunological and surfactant protein genes and the incidence of severe viral infection and level of infection-related morbidity among preterm infants [50,51]. Also, pre-existing impairments in lung function have also been attributed to increased susceptibility to severe viral infection and infection-related morbidity among preterm infants, particularly during early life [5254].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Previous genetic studies have demonstrated a significant association between the inherited polymorphisms in several immunological and surfactant protein genes and the incidence of severe viral infection and level of infection-related morbidity among preterm infants [50,51]. Also, pre-existing impairments in lung function have also been attributed to increased susceptibility to severe viral infection and infection-related morbidity among preterm infants, particularly during early life [5254].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Although it is possible that the immature lungs in preterm infants might be particularly susceptible to long-term damage following severe RSV-related respiratory illness during early life [66,73], RSV infection during such a critical period of lung growth and development can also result in chronic alterations and remodelling of the developing airways independent of pre-existing neonatal factors [50,72]. The underlying mechanisms through which RSV could promote the development of suboptimal lung health and function later in life are yet to be fully elucidated.…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…61,97 Preterm infants with poor initial IFNγ responses may therefore have more severe symptoms upon LRI viral infections in infancy and beyond. Finally, a genetic susceptibility to morbidity after RSV infection may also contribute to severity of disease after LRI, 98 and it is possible that such associations exist with HMPV.…”
Section: Hmpv In Preterm Infantsmentioning
confidence: 99%
“…To assess whether some premature infants are genetically predisposed to clinical bronchiolitis, DRYSDALE et al [90] followed infants discharged from a single maternity unit, and tested nasopharyngeal aspirates whenever infants had a lower respiratory tract infection. When these data were linked to 11 single nucleotide polymorphisms, an association was found between an single nucleotide polymorphisms in ADAM33 and increased risk of developing an RSV-associated lower respiratory tract infection.…”
Section: Viral Infectionsmentioning
confidence: 99%